Removal of Phenols by Highly Active Periodate on Carbon Nanotubes: A Mechanistic Investigation - Jiali Peng; Peng Zhou; Hongyu Zhou; Bingkun Huang; Sun, Minglu; He, Chuan-Shu; Heng Zhang; Zhimin Ao; Liu, Wen; Bo Lai (Environmental Science & Technology, 2023)
Carbon nanotubes (CNTs) and their derivatives have been widely exploited to activate various oxidants for environmental remediation. However, the intrinsic mechanism of CNTs-driven periodate (PI) activation remains ambiguous, which significantly impedes their scientific progress toward practical application. Here, we found that CNTs can strongly boost PI activation for the oxidation of various phenols. Reactive oxygen species analysis, in situ Raman characterization, galvanic oxidation process experiments, and electrochemical tests revealed that CNTs could activate PI to form high-potential metastable intermediates (CNTs–PI*) rather than produce free radicals and 1O2, thereby facilitating direct electron transfer from the pollutants to PI. Additionally, we analyzed quantitative structure–activity relationships between rate constants of phenols oxidation and double descriptors (e.g., Hammett constants and logarithm of the octanol–water partition coefficient). The adsorption of phenols on CNT surfaces and their electronic properties are critical factors affecting the oxidation process. Besides, in the CNTs/PI system, phenol adsorbed the CNT surfaces was oxidized by the CNTs–PI* complexes, and products were mainly generated via the coupling reaction of phenoxyl radical. Most of the products adsorbed and accumulated on the CNT surfaces realized phenol removal from the bulk solution. Such a unique non-mineralization removal process achieved an extremely high apparent electron utilization efficiency of 378%. The activity evaluation and theoretical calculations of CNT derivatives confirmed that the carbonyl/ketonic functional groups and double-vacancy defects of the CNTs were the primary active sites, where high-oxidation-potential CNTs–PI* were formed. Further, the PI species could achieve a stoichiometric decomposition into iodate, a safe sink of iodine species, without the generation of typical iodinated byproducts. Our discovery provides new mechanistic insight into CNTs-driven PI activation for the green future of environmental remediation.